The Influence of Sex and Physical Activity Level on the Modulation of Pain Perception in Response to Transcutaneous Spinal Direct Current Stimulation - Gibson, Jessica (Université d'Ottawa / University of Ottawa, 2018)
Transcutaneous spinal direct current stimulation (tsDCS) is a non-invasive technique that can be used to modulate spinal function. It consists of applying a low-level direct current (DC) across the skin to modulate spinal excitability using surface electrodes. Recent research indicates that this technique can relieve musculoskeletal pain. In this study, we investigate the effect of a 20-min anodal tsDCS (2.5 mA) protocol applied over the thoracic spine on pressure pain threshold (PPT) measured in the thigh, leg and foot in healthy young adults. One primary focus of this study was to determine whether physical activity level, as a potential modulator of pain perception, could influence individual responses to tsDCS. A secondary aim was to also address the role of sex as another potential modulator of pain response. Thirty-five healthy young adults (age 18-35) were recruited for this study. Participants were assigned to either a moderately active (n=21, 12 females), or highly active group (n=14, 8 females) based on a self-report questionnaire (International Physical Activity Questionnaire). The effects were determined by comparing PPT measures at the three sites (thigh, leg, foot) at three time points with respect to tsDCS application: T0: before, T1: immediately after, and T2: 30 min post-application. Results from a multivariate analysis of variance revealed a large main effect of time (F=5.3, p<0.001) on PPTs. Univariate tests (F>16.2, p<0.001) confirmed that PPTs were significantly elevated post-application. In addition, the analysis revealed a significant “Group X Time” interaction (F=2.8, p=0.03), which was explained by a larger elevation in PPTs (thigh site) in the highly active group when compared to the moderately active group. No main effect or interaction was found for sex. Altogether, these results confirmed the anti-nociceptive effects of tsDCS application on mechanical pain threshold and further point to the importance of physical activity as a personal factor susceptible to modulate response to tsDCS.
Keywords: pain; tsDCS; physical activity level; neurostimulation